A study on the transient stability improvement using HVDC-light: article / Mohd Zaimi Mohd Yusof - Mohd Yusof, Mohd Zaimi (2007)
The understanding of the transient stability on power systems is very important to power engineer. Theoretically, there were two types of stability in power systems which are steady-state stability and transient stability. Since transient stability gives a big impact to power systems operation, so, the study on the transient stability is conducted. There were many Flexible AC Transmission Systems (FACTS) devices that can be used to improve the transient stability on the power system network, such as Unified Power Flow Controller (UPFC), Static VAR Compensator (SVC), Thyristor-Controlled Series Capacitor (TCSC), Dynamic Voltage Restorer (DVR), High Voltage Direct Current – Light (HVDC-Light) and so on. HVDC-Light was an idea to connect the power network from Bakun to peninsular Malaysia through the submarine cable.